A Study to Assess the Impact of Training Program Regarding Hypertension on Level of Knowledge and Practice among Accredited Social Health Activist in Selected Rural Area of Mumbai - O, Shalini; Solomon, Smriti G. (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: This study examines how training affects hypertension (HTN) knowledge and practice among Accredited Social Health Activists (ASHAs) in rural Mumbai. Methods: Researchers employed quantitative evaluative research in this study. The researcher used a time series pre- and post-test. This study used random and selective sampling. Study sample size was 500. Frequency and percentage explained sample and all demographic characteristics. Mean and standard deviation explained variables’ dimensions and t-test was used on paired data. Chi-square test was used. Result: Most 317 (63.4%) had poor post-test 1 knowledge scores. Most 261 (52.2%) exhibited poor post-test 2 knowledge. 37.8% of 189 had an average knowledge score after test 3. 72.6% of 363 had poor post-test 1 practicing. 47.4% of 237 had bad post-test 2 practicing scores. 48.6% of 243 had an average practicing score after test 3 knowledge score “t” test value: 10.24, df 499, P < 0.00001. Results show considerable efficiency (P < 0.05). The t-test value for pre- and post-test 2 (O3) knowledge score was 13.02, df 499, P < 0.00001. Results show considerable efficiency (P < 0.05). The pre- and post-test 3 (O4) knowledge score t-test result was 21.34, df 499, and P < 0.00001. Results show considerable efficiency (P < 0.05). The pre- and post-test 1 (O2) practice score t-test was 9.68, df 499, and P = 0.00001. Results show considerable efficiency (P < 0.05) and pre- and post-test 2 (O3) practice score “t” test value: 16.925, df 499, and P = 0.00001. Results show considerable efficiency (P < 0.05). The t-test for pre- and post-test 3 (O4) practice score was 27.54, df 499, and P = 0.00001. Results show considerable efficiency (P < 0.05). Conclusion: This study shows that the HTN training program improves ASHA knowledge and practice scores. ASHA knowledge and practice scores improve.